How has alcohol advertising in traditional and online media in Australia changed? Trends in advertising expenditure 1997–2011. (19th June 2015) - White, Victoria; Faulkner, Agatha; Coomber, Kerri; Azar, Denise; Room, Robin; Livingston, Michael; Chikritzhs, Tanya; Wakefield, Melanie
Abstract Introduction and Aims The aim of this study was to determine changes in advertising expenditures across eight media channels for the four main alcohol beverage types and alcohol retailers in Australia. Design and Methods Yearly advertising expenditures between January 1997 and December 2011 obtained from a leading media‐monitoring company. Media channels assessed were: free‐to‐air television, newspapers, magazines, radio, outdoors (billboards), cinema, direct mail (from 2005) and online (from 2008). Data were categorised into alcohol retailers (e.g. supermarkets, off‐licences) or four alcoholic beverage types (beer, wine, spirits, premixed spirits/cider). Regression analyses examined associations between year and expenditure. Results Total alcohol advertising expenditure peaked in 2007, then declined to 2011 (P = 0.02). Television advertising expenditure declined between 2000 and 2011 (P < 0.001), while outdoor advertising expenditure increased between 1997 and 2007. Alcohol retailers' advertising expenditure increased over time (P < 0.001), and from the mid‐2000s exceeded expenditure for any single beverage category. For both beer and spirits, television advertising expenditure declined over time (beer: P < 0.001; spirits: P < 0.001) while outdoor advertising expenditure increased (beer: P < 0.001; spirits: P = 0.02). However, the number of advertised beer (P < 0.001), spirits (P < 0.001) and wine (P = 0.01) products increased over time. Discussion and Conclusions Retailers are playing an increasing role in advertising alcohol. As our study excluded non‐traditional advertising media (e.g. sponsorships, in‐store) we cannot determine whether declines in television advertising have been offset by increases in advertising in newer media channels. However, our findings that media channels used for alcohol advertising have changed over time highlights the need for adequate controls on alcohol advertising in all media channels. [White V, Faulkner A, Coomber K, Azar D, Room R, Livingston M, Chikritzhs T, Wakefield M. How has alcohol advertising in traditional and online media in Australia changed? Trends in advertising expenditure 1997–2011. Drug Alcohol Rev 2015]2015;34:521–530